Indicial (Palíndromo, 2023)
Visual essay based on the artist's book INDICIAL 2, which starts with the italics, drawings, and overwritten notes on the pages of Maurice Blanchot's book The Book to Come, revealing the passage indexes along the way of reading.
Keywords: visual essay; visual arts; arts